Tecendo redes, construindo laços de solidariedade: a formação de famílias negras, a prática do compadrio e a morte de escravizados e libertos no cariri paraibano (São João do Cariri/1850-1872) - Cavalcante, Eduardo Queiroz (2015)
In this text discussed the formation of black families and relations of cronyism established by enslaved the Freguesia de Nossa Senhora dos Milagres, located in the current city of the São João do Cariri, located in the Paraiba cariri, between the years 1850 and 1872. To this end was made study of the Vila Real de São João do Cariri analyzing the presence of the enslaved population in this locality, in order to understand the relationships of solidarity established from the ritual ties of marriage and spiritual kinship. The proposed discussion is based on the Social History, whose research focus the enslaved, using the concept of experience proposed by Thompson. For the construction of the narrative of the nineteenth century period was essential to use the ecclesiastical documents, such as baptism and death seats; the notary records as inventories of Province of President reports and the 1st Brazilian Population Census of 1872. With the passing of these sources show the importance of slavery within Paraiba, especially in Cariri, thus we highlight the Vila de São João do Cariri economy in the imperial period, driven by livestock and by the enslaved presence in this region. These slaves constituted families (parent or nuclear) and established crony relationships with people higher in the social hierarchy and often relatives of their masters. We note the various causes of the deaths of the captives too, the site of his burial, and the clothes that used to be buried. This study is linked to the Research Line Regional History, and helps to extend our knowledge of the history of enslaved and freed in nineteenth century of Brazil.